Simbol Tradisi Megengan Bagi Warga Dusun Curah Pecak - Lisa Nur Rizki Wulandari; Muhammad Fadhillilah Akbar; Shinta Birbi Kaniasari (Student Research Journal, 2023)
This paper discusses the symbolic meaning of the megengan tradition for the Javanese people, especially the residents of the Bulum Pecak Hamlet, Purwoharjo District. Megengan is a tradition carried out before the month of Ramadan. Many people still maintain and carry out the megengan tradition. Along with the times, many residents of the Bulum Pecak hamlet carry out this tradition according to what was passed down from their ancestors, and quite a number of people carry out this tradition but use a more practical method. From the phenomena that exist, it can be analyzed the meaning of the symbol of the megengan tradition for the people in Curah Pecak hamlet. This study uses qualitative research using an ethnographic approach. The location that the author has chosen is in the hamlet of Bulk Bulk, Purwoharjo District. There are local people who carry out this tradition in accordance with the teachings of their ancestors carefully, but the majority of people who are older, for people who are the millennial generation, continue to carry out the megengan tradition in a more practical way. Each individual carries out the tradition according to the individual's meaning of a symbol.